MyTukxi: low cost smart charging for small scale EVs - Quintal, Filipe (2022)
As the electrification of the transportation sector grows the electric grid must handle the new load resulting from electric vehicles (EV) charging. The integration of this new load in the grid has been subject to work in the smart-charging research field, however, while normal-sized EVs often offer chargers or other functions that support smart-charging, smaller EVs do not, which could be problem atic. Especially considering that the consumption of small EV when aggregated can be significant. This article presents the motivation and development behind the development of MyTukxi, a hardware and software system that aims at implementing smart-charging algorithms for low consuming electric vehicles (EV), interacting with drivers to compensate for the lack of charging control in such vehicles.